2009
DOI: 10.1177/0146167208327217
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Benefits of Feeling Free: Disbelief in Free Will Increases Aggression and Reduces Helpfulness

Abstract: Laypersons' belief in free will may foster a sense of thoughtful reflection and willingness to exert energy, thereby promoting helpfulness and reducing aggression, and so disbelief in free will may make behavior more reliant on selfish, automatic impulses and therefore less socially desirable. Three studies tested the hypothesis that disbelief in free will would be linked with decreased helping and increased aggression. In Experiment 1, induced disbelief in free will reduced willingness to help others. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
363
3
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(393 citation statements)
references
References 25 publications
13
363
3
14
Order By: Relevance
“…Exposure to anti-free will messages can incite selfishness (8) and aggression (9), both of which have bases in morality (5,10). Chiefly related to the present investigation, treatments that weaken the belief in free will, compared with leaving it unchanged, incite more unethical behavior (e.g., in the form of cheating) (11) and reduce support for harsh punishment for criminals (e.g., by recommending shorter prison sentences) (12).…”
mentioning
confidence: 81%
“…Exposure to anti-free will messages can incite selfishness (8) and aggression (9), both of which have bases in morality (5,10). Chiefly related to the present investigation, treatments that weaken the belief in free will, compared with leaving it unchanged, incite more unethical behavior (e.g., in the form of cheating) (11) and reduce support for harsh punishment for criminals (e.g., by recommending shorter prison sentences) (12).…”
mentioning
confidence: 81%
“…Some studies link compatibilist and incompatibilist free will models to moral behaviour (e.g. [58,59]), although none here study the implications of folk philosophy of mind with respect to the belief and value of mind itself (irrespective of its dependency on or otherwise independence from the material world). There is however much related research existent in the literature concerning the negation of belief in mind (e.g.…”
Section: Consequences Of the Evolutionary Development Of An Internal mentioning
confidence: 99%
“…Finally, participants completed items used in previous research to manipulate or measure free will, including two from Baumeister et al (2009) determinism/free will manipulation ("I am able to override the genetic and environmental factors that sometimes influence my behaviors", "All behavior is determined by brain activity, which in turn is determined by a combination of environmental and genetic factors"-reversed scored), three from Stroessner and Green (1990) Free Will-Determinism Scale-Libertarianism Factor ("I will have free will all of my life", "I have free will in life, regardless of group expectations or pressures"; "I am free to make choices in Science Publications JSS my life regardless of social conditions") and one item ("I have free will even when my choices are limited by external circumstances") that loaded on the free will factor from the Rakos et al (2008). A 5-point scale, ranging from "strongly disagree" to "strongly agree" was used for all of the agency and free will items.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Baumeister and colleagues reported that exposure to a deterministic perspective decreased the likelihood of helping (Baumeister et al, 2009) and increased the likelihood of cheating (Vohs and Schooler, 2008). Believing in free will has also been positively related to ratings of employee performance (Stillman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation